Preparation and Characterization of Co-Mo/γ-Al2O3, Ni-Mo/γ-Al2O3 and (Co/Ni)-Mo/γ-Al2O3 Metal Oxides by Sol-Gel Process - Figen, H. E.; Baykara, S. Z. (POLISH ACAD SCIENCES INST PHYSICS, 2012)
In this study, Co-Mo/gamma-Al2O3, Ni-Mo/gamma-Al2O3 and (Co/Ni)-Mo/gamma-Al2O3 metal oxides have been prepared by the sol-gel process using citric acid and calcined at 800 degrees C for 5 h. Phases of synthesized materials were characterized with X-ray diffraction. Morphological analysis and elemental composition of oxides were determined by scanning electron microscope and energy dispersion spectroscopy. Surface analyses of the metal oxides have been studied using the Brunner-Emmett-Teller surface analyzer. Effects of substitution of cobalt and nickel together on the physical properties of the synthesized oxides were also investigated.
Keywords: SMALL MOO3 ADDITIONS; NICKEL-CATALYSTS; HYDROCARBONS; REDUCTION; Physics